Удосконалення технології коньячних виноматеріалів - Мамай, Ольга Іванівна; Луцькова, Вікторія Анатоліївна; Яковенко, Тетяна Олександрівна; Зубкова, Катерина Віталіївна; Стоянова, Ольга Вікторівна; Mamai, Olha; Lutskova, Viktoriia; Yakovenko, Tetiana; Zubkova, Kateryna; Stoianova, Olha (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Удосконалено технологію виробництва коньячних виноматеріалів на основі сировинної бази Херсонської та Миколаївської областей. Встановлено, що використання суміші сортів винограду Рислінг і Аліготе створює передумови для формування виноматеріалів із високим потенціалом у виробництві коньячних спиртів. Найбільш ефективними способами освітлення сусла є комбіновані методи обробки, зокрема препаратами на основі діоксиду кремнію та білкових речовин, що позитивно відображається на смако-ароматичному профілі та інших органолептичних характеристиках коньячних виноматеріалів. Показано, що спеціалізовані штами дріжджів забезпечують більш повне та кероване зброджування сусла порівняно з дикою мікрофлорою, формуючи виноматеріали з оптимальною об’ємною часткою спирту, низьким залишковим вмістом цукрів і високими органолептичними показниками. Це підтверджує доцільність застосування селекційних дріжджів у виробництві коньячних виноматеріалів. Отриманий коньячний виноматеріал відповідає за фізико-хімічними показниками вимогам нормативних документів. /// EN: The technology for the production of cognac wine materials has been improved based on the raw material base of the Kherson and Mykolaiv regions. It has been established that the use of a mixture of Riesling and Aligote grape varieties creates the prerequisites for the formation of wine materials with a high potential in the production of cognac spirits. Studies have confirmed the feasibility of using combined technological schemes of wort processing, in particular preparations based on silicon dioxide and protein substances. This approach not only ensures the transparency and stability of the wort, but also has a positive effect on the taste and aroma profile and other organoleptic characteristics of cognac wine materials. In addition, the formation of a denser and more compact sediment is detected, which indicates a higher efficiency of coagulation processes. It has been shown that specialized yeast strains provide more complete and controlled fermentation of wort compared to wild microflora, forming wine materials with an optimal volume fraction of alcohol, low residual sugar content and high organoleptic indicators. This confirms the effectiveness of the use of selective yeast in the production of cognac wine materials. According to the results of the conducted research, the technology of grape processing with the production of cognac wine materials has been improved. The obtained wine material complies with the physical and chemical parameters of DSTU 4645:2006 Cognac wine materials. General technical conditions and Rules for the production of cognacs of Ukraine.
Improvement of cognac wine materials technology
Keywords: сорти винограду; купаж сортів; освітлення сусла; діоксид кремнію; білкові речовини; шта- ми дріжджів; коньячний спирт; grape varieties; blend of varieties; wort clarification; silicon dioxide; protein substances; yeast strains; brandy alcohol